Functional organic fertilizers can alleviate tobacco (Nicotiana tabacum L.) continuous cropping obstacle via ameliorating soil physicochemical properties and bacterial community structure - Chen, Dan; Wang, Mei; Wang, Gang; Zhou, Yujie; Yang, Xiaoe; Li, Jiangzhou; Zhang, Cuiping; Dai, Kuai (Frontiers in Bioengineering and Biotechnology, 2022)
Continuous cropping obstacle (CCO) in tobacco is a prevail and intractable issue and has not been effectively solved till now. Exploring environmental-friendly and sustainable solutions to CCO, such as, the application of (bio-) organic fertilizers, is favored by researchers. In order to study the effects of functional organic fertilizers (FOFs) on tobacco CCO, five types of fertilizers (CF: tobacco-special chemical fertilizers; VOF: vermicompost-based FOF; HOF: humic acid-based FOF; WOF: wood biochar-based FOF; COF: compound FOF) were applied in a tobacco continuous cropping field with red soil in our study. The tobacco plant agronomic traits, leaf yield, economic value, and chemical quality (nicotine, total sugar, K2O, Cl contents, etc.) were evaluated via the continuous flow method. Meanwhile, we determined rhizosphere soil physicochemical properties, phenolic acids content, and bacterial community diversity by high-throughput sequencing. The results showed that FOFs improved the tobacco plant agronomic traits, leaf yield (by 2.9–42.8%), value (by 1.2–47.4%), and chemical quality compared with CF. More contents of NH4+-N, available P, available K were discovered in the rhizosphere soil in VOF, HOF, and WOF. The rhizosphere sinapic acid and total phenolic acids contents declined in FOFs treatments (1.23–1.56 and 7.95–8.43 mg kg–1 dry soil, respectively) versus in CF (2.01 and 10.10 mg kg–1 dry soil, respectively). Moreover, the rhizosphere bacterial community structure changed under FOFs functions, with beneficial microbes Actinobacteria, Firmicutes, Streptomyces and Bacillus increased, and harmful microbes Acidobacteria and Gemmatimonadota decreased in abundance. There was a positive correlation between the tobacco leaf yield and soil NH4+-N, TC contents, and the relative abundance of Proteobacteria and Actinobacteriota. In summary, the application of VOF and WOF is a modest, practicable, and environmental-friendly strategy in alleviating tobacco CCO from the standpoint of recycling solid waste.